Increased Risk for Cerebral Hypoxia During Immediate Neonatal Transition After Birth in Term Neonates Delivered by Caesarean Section With Prenatal Tobacco Exposure - Wolfsberger, Christina Helene; Bruckner, Marlies; Schwaberger, Bernhard; Mileder, Lukas Peter; Pritisanac, Ena; Hoeller, Nina; Avian, Alexander; Urlesberger, Berndt; Pichler, Gerhard (Frontiers in Pediatrics, 2021)
Introduction: Maternal tobacco smoking during pregnancy is a global health problem leading to an increased risk for fetal and neonatal morbidities. So far, there are no data of the potential impact of maternal smoking during pregnancy on the most vulnerable period after birth – the immediate postnatal transition. The aim of the present study was therefore, to compare cerebral oxygenation during immediate postnatal transition in term neonates with and without prenatal tobacco exposure. Methods: Included in this post-hoc analysis were healthy term neonates, with measurements of cerebral oxygenation (INVOS 5100C) during the first 15 min after birth, and for whom information on maternal smoking behavior during pregnancy was available. Neonates with prenatal tobacco exposure (smoking group) were matched 1:1 according to gestational age (±1 week), birth weight (±100 grams) and hematocrit (±5 %) to neonates without (non-smoking group). Cerebral regional tissue oxygen saturation (crSO2), cerebral fractional tissue oxygen extraction (cFTOE), arterial oxygen saturation (SpO2) and heart rate (HR) within the first 15 min after birth were compared between the two groups. Results: Twelve neonates in the smoking group with a median (IQR) gestational age of 39.1 (38.8–39.3) weeks and a birth weight of 3,155 (2,970–3,472) grams were compared to 12 neonates in the non-smoking group with 39.1 (38.7–39.2) weeks and 3,134 (2,963–3,465) grams. In the smoking group, crSO2 was significantly lower and cFTOE significantly higher until min 5 after birth. HR was significantly higher in the smoking group in min 3 after birth. Beyond this period, there were no significant differences between the two groups. Conclusion: Cerebral oxygenation within the first 5 min after birth was compromised in neonates with prenatal tobacco exposure. This observation suggests a higher risk for cerebral hypoxia immediately after birth due to fetal tobacco exposure.